Did Clinical Trials in Which Erythropoietin Failed to Reduce Acute Myocardial Infarct Size Miss a Narrow Therapeutic Window? - Talan, Mark I. (Public Library of Science, 2012)
BACKGROUND: To test a hypothesis that in negative clinical trials of erythropoietin in patients with acute myocardial infarction (MI) the erythropoietin (rhEPO) could be administered outside narrow therapeutic window. Despite overwhelming evidence of cardioprotective properties of rhEPO in animal studies, the outcomes of recently concluded phase II clinical trials have failed to demonstrate the efficacy of rhEPO in patients with acute MI. However, the time between symptoms onset and rhEPO administration in negative clinical trials was much longer that in successful animal experiments. METHODOLOGY/PRINCIPAL FINDINGS: MI was induced in rats either by a permanent ligation of a descending coronary artery or by a 2-hr occlusion followed by a reperfusion. rhEPO, 3000 IU/kg, was administered intraperitoneally at the time of reperfusion, 4 hrs after beginning of reperfusion, or 6 hrs after permanent occlusion. MI size was measured histologically 24 hrs after coronary occlusion. The area of myocardium at risk was similar among groups. The MI size in untreated rats averaged ∼42% of area at risk, or ∼24% of left ventricle, and was reduced by more than 50% (p<0.001) in rats treated with rhEPO at the time of reperfusion. The MI size was not affected by treatment administered 4 hrs after reperfusion or 6 hrs after permanent coronary occlusion. Therefore, our study in a rat experimental model of MI demonstrates that rhEPO administered within 2 hrs of a coronary occlusion effectively reduces MI size, but when rhEPO was administered following a delay similar to that encountered in clinical trials, it had no effect on MI size. CONCLUSIONS/SIGNIFICANCE: The clinical trials that failed to demonstrate rhEPO efficacy in patients with MI may have missed a narrow therapeutic window defined in animal experiments.